Glycated Albumin Predicts the Risk of Mortality in Type 2 Diabetic Patients on Hemodialysis: Evaluation of a Target Level for Improving Survival. Issue 5 (20th November 2013) - Isshiki, Keiji; Nishio, Toshiki; Isono, Motohide; Makiishi, Tetsuya; Shikano, Tsutomu; Tomita, Koubin; Nishio, Toshiji; Kanasaki, Masami; Maegawa, Hiroshi; Uzu, Takashi
Abstract Glycated albumin (GA) is considered a more reliable marker than glycated hemoglobin (HbA1c) for monitoring glycemic control, particularly in diabetic hemodialysis patients. We investigated the associations of GA, HbA1c, and random serum glucose levels with survival, and evaluated possible targets for improving survival in diabetic hemodialysis patients. In this prospective, longitudinal, observational study, we enrolled 90 diabetic hemodialysis patients across six dialysis centers in Japan. The median duration of follow‐up was 36.0 months (mean follow‐up, 29.8 months; range, 3–36 months). There were 11 deaths during the observation period. GA was a significant predictor for mortality (hazard ratio, 1.143 per 1% increase in GA; 95% confidence interval, 1.011–1.292; P = 0.033), whereas HbA1c and random glucose levels were not predictors for mortality. Receiver operating characteristics curve analysis showed that the cutoff value of GA for predicting the risk of mortality was 25%. In the Kaplan–Meier analysis, the cumulative survival rate was significantly greater in patients with GA ≤25% than in patients with GA >25%. GA predicted the risk of all‐cause and cardiovascular mortality in diabetic hemodialysis patients. Our results suggest that GA ≤25% is an appropriate target for improving survival in diabetic hemodialysis patients.